Grafting to alleviate waterlogging stress in tomato - Bahadur, Anant; Singh, Major; Singh, B. (Indian Horticulture, 2019)
Vegetables like tomato, eggplant, watermelon, melon and cucumber can readily be grafted onto different inter-specific rootstocks to reduce infection by soil-borne pathogens and to enhance the tolerance to abiotic stresses, such as soil salinity, drought, thermal and waterlogging. Grafting of improved cultivars of tomato over eggplant rootstock has ability to tolerate waterlogging condition for 4 days without reduction in fruit yield.